Aeroelastic load simulation of a 3 MW two bladed wind turbine - Carsten Hansen (2014)
Previous development of modern wind turbines has been focused on three bladed turbines. However, two bladed turbines o er some advantages especially for o shore applications. By using additional methods for load reduction, these turbines could signi cantly reduce the cost of electricity from wind energy. A promising approach involves equipping the two bladed turbines with a teeter hub, which can reduce the strain on the drive train enormously. The potential of a teeter hub is compared with the loads of a rigid system in this thesis. Both the extreme loads and fatigue loads are determined and compared according to the IEC 61400-1 guideline.